2021
DOI: 10.3390/molecules26092471
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Allergic Diarrhea Effect of Diosgenin Occurs via Improving Gut Dysbiosis in a Murine Model of Food Allergy

Abstract: Although the anti-allergic and prebiotic activities of diosgenin have been reported, the influence of diosgenin on intestinal immune and epithelial cells remains unclear. As the gut microbiota plays an important role in allergic disorders, this study aimed to investigate whether the anti-allergic diarrhea effect of diosgenin occurs via improving gut dysbiosis. In a murine food allergy model, the density of fecal bacterial growth on de Man, Rogossa and Sharpe (MRS) plates was diminished, and growth on reinforce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Brandt and colleagues [28] described diarrhea after the 3rd and 4th OVA applications. From a total of 10 allergen challenges, Huang et al observed diarrhea symptoms not before the 6th one [71,72]. In a study examining the role of coumarin in OVA anaphylaxis, diarrhea score increased with ongoing allergen challenges [66].…”
Section: Discussionmentioning
confidence: 99%
“…Brandt and colleagues [28] described diarrhea after the 3rd and 4th OVA applications. From a total of 10 allergen challenges, Huang et al observed diarrhea symptoms not before the 6th one [71,72]. In a study examining the role of coumarin in OVA anaphylaxis, diarrhea score increased with ongoing allergen challenges [66].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the 16S rRNA sequencing results, reduced α- and β-diversity indices and altered gut microbiota composition were observed in diarrhea rabbits compared to healthy rabbits. This suggests that diarrhea may be linked to dynamic changes in the composition of the intestinal microbiota (Huang et al, 2021b ). Compared to healthy rabbits, diarrhea rabbits exhibited significantly higher proportions of the phyla Proteobacteria and Firmicutes, whereas significantly lower proportions of Bacteroidetes and Tenericutes.…”
Section: Discussionmentioning
confidence: 99%
“…
25R)-spirost-5-en-3β-Ol (Figure 1), is a phytosteroidal compound extracted from the rhizome of dioscorea. (1) Studies have shown that diosgenin has antieffects on blood lipid, (2) diabetes, (3) thrombus, (4) myocardial ischemia, (5) rheumatoid arthritis, (6) inflammation, (7) allergy, (8) immune regulation. (9) Concurrently, it also has a resisting effect on neoplasm, nephropathy, (10) encephalomyelitis, (11) osteoporosis, (12) Parkinson's disease, (13) Alzheimer's disease, (14) and plays a beneficial role in pulmonary hypertension.
…”
mentioning
confidence: 99%